Bristolian shoots rapids on America's wildest river - Rolston, Holmes, 1932-2025, author; Bristol Herald Courier, publisher (Colorado State University. Libraries, 1967)
Rolston's account of a river run through the Grand Canyon, Lee's Ferry to Lake Mead, July 27-August 5, 1967.
Keywords: Colorado River (Colo,-Mexico); rapids; fauna; natural history; river expeditions; flora; nature; Grand Canyon (Ariz.)